How doctors recognise that their patients are worried: A qualitative study of patient cues. Issue 1 (January 2020) - Giroldi, Esther; Timmerman, Angelique; Veldhuijzen, Wemke; Muris, Jean; van der Vleuten, Cees; van der Weijden, Trudy
Highlights: GP interviews about cue-recognition within the process of reassurance. GPs stress that recognising patients cues is crucial for successful reassurance. GPs expressed noticing non-verbal -, verbal -, and behavioural- and foreknowledge-based cues. Most cues are picked up during the opening and information-gathering phase. GPs' interpretations of cues should always be verified with the patient. Abstract: Objectives: Recognising patient cues indicating worry is essential for successful reassurance. To obtain more insight into the variety and nature of patient cues that may arise in practice, this study explores doctors' reflections on patient cues they recognise during consultations. Methods: We performed a qualitative study during which GPs participated in stimulated recall interviews, using their own video-recorded consultations to enhance reflection. First, we reanalysed an existing dataset of 15 interviews during which GPs elaborated on the doctor-patient interaction. Additionally, 12 GPs were interviewed specifically about recognising patients' cues. Results: GPs described four categories of patient cues that indicate worry. GPs recognised worry based on non-verbal cues such as visible bodily reactions, and verbal cues that can be further categorised by type of worry ( e.g . about serious disease). Moreover, GPs described behavioural cues, e.g . the patient bringing a list of symptoms. Lastly, GPs recognise worry based on prior knowledge about the patient. Conclusions: GPs reflections have given insight into a wide variety of non-verbal -, verbal -, behavioural- and foreknowledge-based cues. Practice implications: The identified cues can guide other clinicians in recognising worries and inform medical communication training and future research on the effectiveness of recognising cues and patient reassurance.